2018
DOI: 10.1136/jclinpath-2018-205320
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of SIRT1 and SOD-1 and the correlation between these levels in various regions of the brains of patients with Alzheimer's disease

Abstract: These findings indicate that the reduced level of SIRT1 in the brains of patients with AD may be related to the decline in SOD-1 and neuropathological changes of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Accumulating evidence demonstrated that Sirt1 plays an important role for neuroprotection in several models of neurodegenerative diseases, such as Alzheimer's disease (AD) (Fujita and Yamashita, 2018), while the level of hippocampal Sirt1 were significantly decreased in patients with AD (Cao et al, 2018). Meanwhile, it has been demonstrated that oxymatrine attenuated hippocampus ischemia/reperfusion injury through upregulation of Sirt1 (Zhou et al, 2018), indicating that Sirt1 acts as a key factor in hippocampal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrated that Sirt1 plays an important role for neuroprotection in several models of neurodegenerative diseases, such as Alzheimer's disease (AD) (Fujita and Yamashita, 2018), while the level of hippocampal Sirt1 were significantly decreased in patients with AD (Cao et al, 2018). Meanwhile, it has been demonstrated that oxymatrine attenuated hippocampus ischemia/reperfusion injury through upregulation of Sirt1 (Zhou et al, 2018), indicating that Sirt1 acts as a key factor in hippocampal damage.…”
Section: Discussionmentioning
confidence: 99%
“…A decline in normal antioxidant defense mechanisms has been observed in the aging brain and in the case of several neurodegenerative diseases. 19 Such a decline increases the vulnerability of the brain to the deleterious effects of oxidative damage; the brains of patients with Alzheimer's disease showed reduced activity of antioxidant enzymes (SOD, catalase, glutathione peroxidase and glutathione reductase) 26,27. Different markers of oxidative stress in the aging brain have been broadly researched, for example 8-OHdG (8-hydroxy-2′-deoxyguanosine) as a biomarker of oxidative DNA damage in the aged brain [28][29][30].…”
mentioning
confidence: 99%
“…A large body of evidence suggests that oxidative stress plays an important part in the pathogenesis of AD (Youssef et al, ). SOD is important antioxidant enzymes protected cellule against damage caused by oxygen‐derived free radicals, by means of removing toxic peroxide metabolites and blocking lipid peroxidation chain reaction (Cao et al, ). The MDA as index of lipid peroxidation has attracted widespread interest, because it appears to offer a means of assessing lipid peroxidation in biological materials (Tian et al, ).…”
Section: Discussionmentioning
confidence: 99%